Essays on international capital flows - Guerin, Selen Sarisoy (Trinity College (Dublin, Ireland). Department of Economics, 2003)
This thesis is a collection of essays on international capital flows. The main motivation for this work was to address a number of relatively unexplored issues within this subject. Four topics were empirically analyzed utilizing a variety of econometric techniques and diverse data sources. Chapter 1 examines the relationship between current accounts and capital accounts in a set of industrial and developing countries. Specifically, the focus is on the link between net private capital inflows and the current account. In the first part of this chapter, panel fixed-effect regressions are employed to test the effect of cyclical net inflow volatility on current account volatility. In the second part, cointegration techniques and causality tests are used to establish causal links between net inflows and current account imbalances. The results indicate that the relationship between current account and net capital inflows differs across industrial and developing countries. Chapter 2 is an empirical examination of the relationship between deposit insurance and private capital inflows in an effort to find support for the hypothesis that the existence of explicit insurance may encourage gross private capital inflows to a country. However, the results of the regression analyses, utilising four different variables to measure private capital inflows, fail to find any statistically significant resuh to support this hypothesis. Chapter 3 investigates the determinants of FDI flows with an emphasis on FDI as a financial flow. FDI has increased in importance in the 1990s and is concentrated in the North and a few South countries as destinations. We try to explain the geographical concentration of FDI inflows by examining North-North, North-South and South-North flows. The resuhs indicate that different host country characteristics have, in general, the same direction of impact but they are different in magnitude for South host countries than they are for North. The standard gravity variables and additional geographical and traderelated variables are significant determinants of bilateral FDI inflows. Chapter 4 examines the role of geography in explaining the spatial allocation of foreign direct investment flows vis a vis patterns in trade flows and portfolio investment. In the empirical part of this chapter, we examine the determinants of North-North, North-South and South-North FDI, trade and portfolio investment flows using a modified gravity model, which allows a direct comparison of the geographical factors that affect each group of bilateral flow. Specifically, we examine the effect of standard gravity variables on trade and portfolio investment flows to highlight any similarities with patterns of FDI flows. Our results indicate that standard gravity variables have the same impact on each bilateral trade and portfolio investment as their impact on FDI. We conclude that geographical factors can explain the spatial allocation of FDI, trade and portfolio investment flows.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin